An Exploration of Derrida's Philosophy of Deconstruction and Its Implications for Education - Ruyu Hung (National Taipei University of Education, 2016)
This paper aims to discuss the post-structural philosopher Jacques Derrida's philosophy of deconstruction and its implications for education. There are four main notions to be investigated: deconstruction, différance, trace and supplement. By interrogating the four notions, the author reveals four implications for education. They are as follows: 1) The deconstruction of the textual structure is to deconstruct the traditions of thought. 2) Reading the Classics in different ways is helpful to increase educational meanings. 3) Imagination about education should go beyond the conventional way of learning by means of "listening, speaking, reading and writing". 4) Playfulness is able to replenish austerity in theorizing ways of life. The author, then, uses three examples concerning gender body politics, library and information science, and the Paul de Man event to explore the dynamics and limits of the deconstruction as a strategy of analyzing the discourse. At the end, the author concludes that the most profound significance of deconstruction lies in continuous self-questioning and self-challenging rather than serving as a tool of straightforward appropriation and application to reality affairs. Otherwise, the notion of deconstruction could lose its dynamical criticality.